Existence of Performing Rights: An Analysis of Implications and Orientations for Café Singers - Akhwan Prayogi; I Gede Agus Kurniawan (SASI, 2023)
Introduction: Performing rights are rights attached to copyright as an integral part of the creation of a work. In the context of copyrights to songs or music, performing rights relate to the need to pay royalties to songwriters or music for attempts to use songs or music commercially.